Early lung ultrasound score to predict noninvasive ventilation needing in neonates from 33 weeks of gestational age: A multicentric study. Issue 9 (20th June 2022) - Perri, Alessandro; Sbordone, Annamaria; Patti, Maria L.; Nobile, Stefano; Tirone, Chiara; Giordano, Lucia; Tana, Milena; D'Andrea, Vito; Priolo, Francesca; Serrao, Francesca; Riccardi, Riccardo; Prontera, Giorgia; et al.
Abstract: Objective: To propose an early lung ultrasound (LUS) score for the prediction of the need for respiratory assistance in newborns of gestational age (GA) ≥ 33 weeks presenting respiratory distress. Study Design and Setting: Multicenter, prospective observational study in third‐level neonatal intensive care units. Patient Selection: Infants with GA ≥ 33 + 0 weeks with respiratory distress within 3 h of life. Methods: Three LUS for each patient were collected: within 3 h of life (T0), at 4–6 h of life (T1), and at the resolution of symptoms (T2). The primary aim was to assess the validity of the early LUS score in predicting the need for continuous positive airway pressure (CPAP). We also evaluated the validity of the score in predicting the need for surfactant, the scores' trend in our population, and any correlation with the duration of ventilation and oxygen therapy. Results: Sixty‐two patients were enrolled in the study. The mean GA was 36 weeks. The receiver operating characteristic analysis for the LUS T0 and T1 yielded area under the curves of 0.91 and 0.82 in predicting the need for CPAP, respectively. LUS score cut off of 6 (sensitivity 84.8%, specificity 86.2%) and 5 (sensitivity 66.7%, specificity 100%) were calculated at T0 and T1, respectively. We found significant correlations between LUS score and respiratory assistance, surfactant administration, and SpO2 /FiO2 ratio. Conclusion: An early LUS score is a good noninvasive predictor of the need for respiratory assistance with CPAP and surfactant administration in newborns with GA ≥ 33 weeks.